Implementation of Education in the Independent Learning Curriculum Based on Ki Hajar Dewantara Education - Torly Amora Jofipasi; Herman Nirwana; Dina Sukma; Jon Efendi (Manajia: Journal of Education and Management, 2025)
This article aims to assess the implementation of education in the current Ki Hajar Dewantara education-based independent learning curriculum. The implementation of educational activities has a huge impact on the nation's progress process, the basis for implementing education is the curriculum. The current curriculum in Indonesia is the Independent Curriculum. The Independent Curriculum is an educational innovation in Indonesia that gives schools and teachers the freedom to design and implement learning processes that suit students' needs and potential. In line with this, Ki Hajar Dewantara's education is also a student-centered educational process. In this research, a literature review is used as the research method. The results of the research show that studying the implementation of the Ki Hajar Dewantara education-based Merdeka Curriculum helps in increasing students' creativity, independence and active participation in the learning process. Apart from that, the application of local cultural values in the independent learning curriculum has a positive impact on strengthening students' identity and character. This research makes an important contribution to the development of more relevant and contextual educational policies and teaching practices in Indonesia.